Modeling the Bond-Slip Effect in RC Column with Plain Reinforcement Bars - Shan, Tilong; Yurdakul, Özgür; Řoutil, Ladislav (Fédération Internationale du Béton (fib) - International Federation for Structural Concrete, 2024)
Reinforced concrete (RC) structures designed and constructed using pre-70s construction practices (i.e., non-conforming details, plain reinforcement bars) often face challenges during earthquakes due to the limited interaction between the plain reinforcement bar and surrounding concrete. The bond-slip effect is widely recognized as a common cause of premature failure in existing RC structures subjected to seismic loads. However, many numerical models overlook the importance of the bond-slip effect. This paper focuses on advancing the numerical modeling of RC columns with plain reinforcement bars, considering the critical bond-slip effect. Experimental data from cantilever columns, specifically designed and constructed with plain reinforcement bars, and subjected to cyclic loading, were gathered from relevant literature studies. Subsequently, advanced numerical models emphasizing the influence of the bond-slip effect were developed in a finite element (FE) environment using ATENA Science software. The numerical results are then presented and compared with the corresponding experimental outcomes. These comparisons highlight a noteworthy agreement between the numerical models for RC columns that consider the bond-slip effect, showing a certain level of precision.
Keywords: Reinforced concrete structures; plain reinforcement bars; bond-slip effect; numerical model; cyclic loading